Abdominal Wall Defects among Mexican American Infants: The Effect of Maternal Nativity - Hibbs, Shayna D. (Ethn Dis, 2016)
BACKGROUND: US-born Mexican American women have greater rates of preterm birth and consequent overall infant mortality than their Mexico-born peers. However, the relation of Mexican American women’s nativity to rates of congenital anomalies is poorly understood. Hispanic ethnicity and young maternal age are well-known risk factors for gastroschisis. OBJECTIVE: To determine the extent to which nativity of Mexican American women is associated with abdominal wall defects. METHODS: Stratified and multivariable logistic regression analyses were performed on the 2003-2004 National Center for Health Statistics linked live birth-infant death cohort. Only Mexican American infants were studied. Maternal variables examined included nativity, age, education, marital status, parity, and prenatal care usage. RESULTS: Infants with US-born Mexican American mothers (n=451,272) had an abdominal wall defect rate of 3.9/10,000 compared with 2.0/10,000 for those with Mexico-born mothers (n=786,878), RR=1.9 (1.5-2.4). Though a greater percentage of US-born (compared wtih Mexico-born) Mexican American mothers were teens, the nativity disparity was actually widest among women in their 20s. The adjusted (controlling for maternal age, education, marital status, parity, and prenatal care) odds ratio of abdominal wall defects among infants of US-born (compared with Mexico-born) Mexican American mothers was 1.6 (1.2-2.0). CONCLUSIONS: US-born Mexican American women have nearly a two-fold greater rate of delivering an infant with an abdominal wall defect than their Mexico-born counterparts. This phenomenon is only partially explained by traditional risk factors and highlights a detrimental impact of lifelong residence in the United States, or something closely related to it, on the pregnancy outcome of Mexican American women.